[PP.22.04] SYSTOLIC BLOOD PRESSURE AND POTASSIUM REGULATION. (September 2017) - Kisters, K.; Reither, L.; Gell, H.; Moser, M.; Pichlkastner, K.; Viebahn, I.; Stossier, H.; Harb, M.; Porta, S.
Abstract : Objective: Medical textbooks mostly underline the reciprocity of H+transport into tissue and K+ transport into blood. Therefore we performed the following study to show that physiological facts in normal life can be different. Design and method: 23 healthy young officier trainees were tested for potassium, pCO2, O2 saturation, Ph value, BE and lactate (PhOX-M, TECOM, Austria), and systolic blood pressure values (Beurer, Ulm, Germany) during the sympatho-adrenal anticipation phase before their first parachute jump. Results: During mental Irritation before the parachute jump, potassium in blood decreases linearly with the increase of calculated free fatty acids ((BE-lactate), r = 0.648, P < 0.01), but due to over-compensatory respiratory control, pH value increases instead of declining. Consequently, no K/pH correlation exists. However, within the normal range of systolic blood pressure values (up to 140 mmHg), potassium declines linearly with increasing systolic blood pressure values (r = 0.47, p < 0.05). The reaction dovetails well with potassium decline proportional to fatty acid increase, both indicating an increased catecholaminergic state. Conclusions: In conclusion a potassium decline in day-to-day mental irritation is dependent on catecholaminergic effects, visibly expressed in increasing systolic blood pressure values. An obvious consequence is that increased systolic blood pressure values during mental irritation could be the onset of chronic potassium loss and should be counteracted preventively.